Analisis Masa Jabatan Kepala Desa Dalam Undang-Undang Nomor 3 Tahun 2024 Junto Undang-Undang Nomor 6 Tahun 2014 Tentang Desa Ditinjau Dari Maslahah Mursalah - Sakdi (YUDHISTIRA : Jurnal Yurisprudensi, Hukum dan Peradilan, 2024)
The change in the term of office of village heads from six years and three terms as stipulated in Law Number 6 of 2014 to eight years and two terms through Law Number 3 of 2024 has given rise to extensive legal and political discourse. This study aims to analyze the implications of this change through an Islamic legal approach with the concept of maslahah mursalah. This study uses a normative legal research method with a qualitative approach, which examines legal norms in laws and regulations as well as relevant Islamic legal doctrines and concepts. The approaches used include a legislative approach to examine changes in legal substance in the two laws, and a conceptual approach to review the principles of maqāṣid al-syarī‘ah and public welfare in the policy of extending the term of office of village heads. The data used are sourced from primary legal materials (laws and regulations), secondary (literature, books, and scientific journals), and tertiary (dictionaries and legal encyclopedias), which are analyzed descriptively and analytically. The research results show that extending the village head's term of office provides benefits in the form of leadership stability, development continuity, efficiency of election costs, and reduced potential for social conflict due to repeated political contestations. However, this change also risks weakening community evaluation mechanisms, hindering leadership regeneration, and creating the potential for concentration of power. Within the framework of maslahah mursalah, this policy is acceptable as long as the benefits outweigh the harms, provided there is strong oversight, active community participation, and trustworthy, transparent, and accountable leadership.